2013
DOI: 10.1007/s00018-013-1374-5
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte growth and sarcomerogenesis at the intercalated disc

Abstract: Cardiomyocytes grow during heart maturation or disease-related cardiac remodeling. We present evidence that the intercalated disc (ID) is integral to both longitudinal and lateral growth: increases in width are accommodated by lateral extension of the plicate tread regions and increases in length by sarcomere insertion within the ID. At the margin between myofibril and the folded membrane of the ID lies a transitional junction through which the thin filaments from the last sarcomere run to the ID membrane and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
70
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 56 publications
8
70
0
Order By: Relevance
“…Our data show an unchanged crest‐crest distance of ≈2 μm in TAC cardiomyocytes, corresponding to the sarcomere length of quiescent myocytes. Because cell size was increased (increased cell capacitance; Figure 3C), sarcomeres were likely inserted during the development of hypertrophy in TAC hearts, as described previously by Wilson and coworkers in dilated cardiomyopathy 34. Although the number of sarcomeres and cell crests per cell increased, the mRNA and protein expression and density of sodium channel clusters remained unchanged.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Our data show an unchanged crest‐crest distance of ≈2 μm in TAC cardiomyocytes, corresponding to the sarcomere length of quiescent myocytes. Because cell size was increased (increased cell capacitance; Figure 3C), sarcomeres were likely inserted during the development of hypertrophy in TAC hearts, as described previously by Wilson and coworkers in dilated cardiomyopathy 34. Although the number of sarcomeres and cell crests per cell increased, the mRNA and protein expression and density of sodium channel clusters remained unchanged.…”
Section: Discussionsupporting
confidence: 64%
“…Similar to natural growth occurring during cardiomyocyte development, growth during cardiac remodeling is achieved by the insertion of sarcomeres flanking the ID 34. Our data show an unchanged crest‐crest distance of ≈2 μm in TAC cardiomyocytes, corresponding to the sarcomere length of quiescent myocytes.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Therefore, despite an increase in the frequency of ICDs with a smaller surface area, the plicae are enlarged, which will act to provide local areas with increased contact surfaces between the two cells. An increase in plicae amplitude has also been recently described as part of the mechanism that promotes myocyte lengthening during development (34) with the scaffold protein N-RAP shown to be instrumental for myofibril assembly (35) and in the adult cardiac myocyte N-RAP is exclusively localized to the ICD (36). Here, we found that N-RAP was upregulated in HF.…”
Section: Structural and Molecular Modifications To The Icds In Hfmentioning
confidence: 59%
“…Before reaching the ICD the thin filaments pass or are attached to an additional structure named the "transitional element" (Bennett et al, 2006), which contains a high amount of a specialized spectrin variant (spectrin IVa; see Wilson et al, 2014). The transitional elements (TE) are further characterized as the region where the sarcomeric titin filaments end and by the presence of ␣-actinin, though of a much lower amount than in the classical Z-line (Wilson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%